2015
DOI: 10.1021/acs.jpcb.5b06861
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Energetic Impact of Non-Natural 7-Deaza-8-Azaadenine and Its 7-Substituted Derivatives on H-Bonding Potential with Uracil in RNA Molecules

Abstract: Abstract:Non-natural (synthetic) nucleobases, including 7-ethynyl-and 7-triazolyl-8-aza-7-deazaadenine, have been introduced in RNA molecules for targeted applications, and have been characterized experimentally. However, no theoretical characterization of the impact of these modifications on the structure and energetics of the corresponding H-bonded base pair is available. To fill this gap, we performed quantum mechanics calculations, starting with the analysis of the impact of the 8-aza-7-deaza modification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…35,39,41,44,48−50 In the present study, we also derived the interaction energies in water, which were calculated using the same recipe as suggested by Sponer and co-workers. 48,74 To have an immediate and intuitive understanding of the impact of a specific modification, we introduced the modification energy, E mod , 36,38 defined as the energy difference between the interaction energy of the modified and that of the corresponding unmodified base pair (in this specific case, the Z:P base pair) Table 1. Geometry and Interaction Energy a of cWW Z:P and tWW Z:iP/iZ:P Base Pairs with 5-Substituted Z. Geometry and interaction energy of cWW G:C and tWW iG:C/G:iC are also reported for comparison.…”
Section: ■ Models and Computational Detailsmentioning
confidence: 99%
“…35,39,41,44,48−50 In the present study, we also derived the interaction energies in water, which were calculated using the same recipe as suggested by Sponer and co-workers. 48,74 To have an immediate and intuitive understanding of the impact of a specific modification, we introduced the modification energy, E mod , 36,38 defined as the energy difference between the interaction energy of the modified and that of the corresponding unmodified base pair (in this specific case, the Z:P base pair) Table 1. Geometry and Interaction Energy a of cWW Z:P and tWW Z:iP/iZ:P Base Pairs with 5-Substituted Z. Geometry and interaction energy of cWW G:C and tWW iG:C/G:iC are also reported for comparison.…”
Section: ■ Models and Computational Detailsmentioning
confidence: 99%
“…We notice that both DAA and DAiG feature a N6 amino group, which can directly interact with the C7-substituents, as indicated by the modification in the electron density around it (Figure 6). [14]…”
Section: Chembiochemmentioning
confidence: 99%
“…[12] Our subsequent quantum mechanics analysis confirmed that the modified 7-deaza-8-azaadenine (DAA) and its 7-substituted derivatives have a negligible impact on the geometry and interaction energy of the base pairs they make with uracil, both in antiparallel and parallel doublehelix strands, and provided a theoretical explanation for that. [14] Similarly, several 7-deaza-8-aza analogues of guanine have also been synthesized and used in different applications in the last couple of decades, especially in the context of DNA. [15] A variety of 7-substituted 7-deaza-8-azaguanine (abbreviated here as DAG) residues, including 7-halogen derivatives, have been shown to stabilize the classical antiparallel DNA duplex, [16] while 7-deaza-8azaisoguanine (abbreviated here as DAiG) and its 7-halogen derivatives have been shown to stabilize the parallel DNA duplex when paired to self-complementary strands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a rather standard approach used in this kind of calculations. [69][70][71][72][73][74] download file view on ChemRxiv Manuscript.docx (2.22 MiB)…”
Section: Computational Detailsmentioning
confidence: 99%